PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM JUAL - BELI TELEPON SELULER TANPA GARANSI DI PASAR GELAP (BLACK MARKET) - Yogiartha, Gde Manik; Wirta Griadhi, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
Legal protection of consumers in the sale - buy a cell phone without a guarantee on the black market (Black Market) viewed from the perspective of consumer protection laws. The problem is how the legal protection of consumers in selling - buying a cell phone without a guarantee on the black market? and how the sanctions against the sale of mobile phones without a warranty on the black market?. The method of writing using descriptive normative methods. The results related to the Act - Act No. 8 of 1999 on Consumer Protection and Regulation of the Minister of Trade No. 19/M-DAG/PER/5/2009 on Registration Instructions for Use (Manual) and Warranty Card / Aftermarket Warranty For Products In Indonesian telematics and Electronics. Trade in violation of the law and done outside official channels, can be referred to as a black market.
Keywords: Consumer Protection, Sale, Warranty, Black Market.